DOBUTAMINE USAGE IN CARDIOLOGICAL PRACTICE - M. Yu. Giljarov (Рациональная фармакотерапия в кардиологии, 2016)
Dobutamine is inotropic drug indicated in systolic dysfunction. Data on dobutamine pharmacology, its effects on hemodynamics, coronary and peripheral blood flow, myocardial electrophysiology are presented. Clinical usage and the main contraindications of dobutamine are discussed.